The Use of Cohesion of Susilo Bambang Yudhoyono’s Speech in APEC Economic Leader Conference in Bali - Muthoharoh, Khusnul; Nur Rohmah, Galuh (Kirana Publisher (KNPub), 2022)
Cohesion in discourse is important to know the coherence of discourse. In this study, intends to analyze the types of cohesive devices and the function of cohesive devices used in Susilo Bambang Yudhoyono’s speech. The research design in this study is descriptive qualitative. The object of the research are transcription of Susilo Bambang Yudhoyono’s speech. Researcher investigator is the primary instruments for gathering and analyzing data. There are four main steps to analyzing the data; identifying the sentences, classifying the cohesion of the speech into Halliday and Hassan’s theory, explaining the data and concluding the data. There are three types of cohesion used in the speech. The result of this research is he mostly used in the speech is reference. The majority used is personal reference. It shows that the speaker wants to make cooperate with the listener or audiences of the conference. Furthermore The mostly used in the speech is subject.